Empowerment Program In Improving Healthy Behavior In Students Throuh PHBS In State Elementary Schools (SD) 25 Ternate City - Hairudin La Patilaiya (International Journal Of Community Service, 2021)
Clean and healthy living behavior (PHBS) in schools is an activity to empower students, teachers and the community of the school environment to want to adopt a healthy lifestyle, thus creating a healthy school. School age children are a critical age, because at that age a child is vulnerable to health problems. Students in elementary schools are the right targets to be objects of counseling about clean and healthy living behaviors (PHBS) with the aim of increasing students' knowledge and understanding of clean and healthy living behaviors. The activity was carried out on January 7, 2020 at the 25 state elementary schools in Ternate City. The results of counseling were an increase in knowledge from the results of the pre-test 35.5% and the post-test 65.5% about PHBS from 27 students with 10 questions.